Ice hockey specific strenght training with elastic bands - Nieminen, V. (2012)
The importance of muscular strength training during the career of all athletes is remarkable in competitive sports. Actual strength training can be started when children are still quite young. Research has proven that elastic resistance can provide similar properties than free weights or weight machines, making it ideal and effective device across ages from sedentary people to elite athletes Elastic resistance makes it possible for muscles to be strengthened along sport specific patterns throughout the motion. The video project and all its material were produced as a commission for the International Ice Hockey Development Centre. The purpose of these elastic band exercise project was to provide ice hockey coaches and players with a tool that addresses hockey strength training efficiently, diversely and specifically, regardless of the training location. Further, the idea of elastic bands is to provide a safe and easy way for young athletes to start strength training. The starting point was to get know the exercise device and define primary muscles taking part in ice hockey performance. After that, exercises applicable to on ice performance and following similar movement paths were conceived. The main idea was to improve ice hockey game performance. Altogether there are 81 exercises, all of which have been filmed and are available on the Hockey Centre Internet server. All the movements have been designed to activate muscles used during an optimal hockey performance. The exercises have been divided into lower body, core, and upper body exercises. Many of the exercises activate the entire body. The device has been declared to be effective and beneficial in practical use and is being widely used in ice hockey practices. Elastic band exercises help players recognize the muscles used in hockey and activate them in a correct sequence required in an optimal hockey performance. In addition, elastic device has had a central role in the coaching seminars held by the Finnish Ice Hockey Association.